Challenging or Conforming to the Norms of Victorian Society: Queen Victoria’s Stance on Women’s Social Status - Arildsen, Emilie (Leviathan: Interdisciplinary Journal in English, 2018)
Queen Victoria represents a personality split between the values of the submissive contemporary woman and the values of a powerful monarch. She was head of her country, but a married woman too, and this combination entailed situations that were difficult to navigate while retaining the values of the ideal Victorian woman and simultaneously meeting her duties as queen. I claim that by combining her two roles and becoming the mother of the Empire, Queen Victoria ultimately bettered women’s social status by influencing the mindset of her contemporary women. Her influence is apparent in writings of both feminists such as Millicent Garrett Fawcett and conservative Sarah Stickney Ellis as well as in the lives of her own daughters.